Acarofauna (Acari) associada a cultura do guaraná (Paullinia cupana Kunth, Sapindaceae) na região do médio Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2021)
Mites are important components in plant crowns. In agricultural crops in the state of Amazonas, the presence of the forest environment influencing biodiversity in the agroecosystem is characteristic. In the case of the guaraná plant (Paullinia cupana Kunth, Sapindaceae), a native Amazonian plant with economic, cultural, and social importance, no research was conducted to know the association of these organisms with this culture. This study aimed to investigate the diversity of mites (Acari) associated with guarana culture in the middle Amazon region, as well as to verify the influence of the cultivation system on the community of these organisms. A survey was carried out in 20 areas of guaraná cultivation in six municipalities: Itacoatiara (five areas), Urucará (four areas), Itapiranga (two areas), Maués (four areas), São Sebastião do Uatumã (three areas) and Urucurituba (two areas), being sampled ten leaves of 15 individuals in each area. Mites from 61 species, belonging to 15 families, were recorded. Phytoseiidae and Tarsonemidae were the families with the highest richness, 23 and 12 species, respectively. Asca sp.1 (Ascidae) was the most abundant species among all recorded mite species, 205 mites. Among the mites of the Phytoseiidae, an important family of predatory mites, the most abundant was Typhlodromips angustus Guanilo & Moraes, with 170 specimens collected. To verify the influence of cultivation on the mite fauna, two collections were carried out in three areas in the municipality of Itacoatiara, AM: (a) conventional cultivation with the use of chemical pesticides (CCQ); (b) conventional cultivation without the use of chemical pesticides (CSQ) and (c) agroforestry cultivation (CAF), sampled ten leaves of 15 individuals per area. A total of 733 mites from 51 species, belonging to 14 families, were recorded. In the CSQ area, 318 mites belonging to 37 species from 10 families were recorded; CCQ, 277 mites belonging to 24 species from 9 families; CAF, 138 mites from 27 species belonging to 12 families. Phytoseiidae was the richest family, 19 species, followed by Tarsonemidae (12). The most abundant species were Xenotarsonemus sp.2 (124 individuals) and Xenotarsonemus sp.1 (104) (Tarsonemidae). Typhodromips angustus and Asca sp.1 were the most abundant predators, with 76 and 47 mites, respectively. CAF recorded the highest diversity index, despite the richness and abundance recorded in the CSQ area being higher in relation to the other areas. A new species of Amblydromalus Chant & McMurtry is described and illustrated based on adults of both sexes of individuals associated with naturally vegetated plants, exotic fruits, and plants not cultivated in guarana crops in Amazon biome. Type material from A. akiri Nuvoloni, Lofego, Rezende & Feres was re-examined and the number of arrows and genu III chaetotaxy were corrected. Notes on the occurrence of Amblydromalus in South America and key to species of this genus were also provided. This was the first study to know the mite fauna associated with the guaraná culture. It was possible to verify a great diversity of mites associated with this plant, mainly from the Phytosesiidae and Tarsonemidae families.
Keywords: Guaraná - Doenças e pragas; Ácaros de plantas; CIENCIAS AGRARIAS; Amazônia; Levantamento; Agroecossistema; Espécie nova